Effectiveness of Abdominal Compresses on Constipation in Stroke Patients in the Neuro Room of Prof. Dr. Aloei Saboe Hospital - Pebriani Mustapa; Fadli Syamsuddin; Rini Asnawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Constipation is an elimination problem that often occurs in stroke patients due to neurological disorders, immobilization, and a low-fiber diet. This condition can decrease comfort, hinder recovery, and trigger complications such as fecal impaction. Warm abdominal compresses are a nonpharmacological intervention that can improve intestinal motility. Objective: To determine the effect of abdominal compresses on the rate of constipation in stroke patients. Methods: This study used a pre-experimental design with a one group pretest-posttest design approach. The sample consisted of 15 stroke patients who were selected using accidental sampling techniques in the Neuro Room of Prof. Dr. Aloei Saboe Gorontalo Hospital. The intervention was in the form of abdominal compresses with Warm Water Zak at 40–50°C for 20 minutes every day for three days. The level of constipation was measured using the Constipation Assessment Scale (CAS). The normality test used the Shapiro-Wilk test and the statistical analysis used the Wilcoxon test. Results: After a warm compress intervention in the abdomen for 3 days, the category of non-constipation increased from 0 respondents (0%) to 2 respondents (11.8%), mild constipation of 2 respondents (11.8%) increased to 11 respondents (64.7%), moderate constipation of 10 respondents (58.8%) decreased to 2 respondents (17.6%), and severe constipation of 4 respondents (29.4%) decreased to 2 respondents (5.9%). The Wilcoxon test showed a value of p = 0.000 (p< 0.05), indicating a significant effect of abdominal compression on the reduction of constipation. Conclusion: Abdominal compresses are effective in lowering the rate of constipation in stroke patients. This intervention is safe, easy to implement, and can be recommended as a nonpharmacological nursing measure to improve elimination function in stroke patients.